Rebetiko in diaspora: The London Rebetiko scene. Issue 1 (1st April 2022) - Nissen, James
One of the most active rebetiko scenes outside Greece is in London. Drawing on ethnographic fieldwork at Rebetiko Carnival, engagement with the scene between 2014 and 2020, and personal interviews with key musicians, this article examines the meanings and the unique features of Rebetiko in London. It shows the roles of music in forming a diasporic musical community and maintaining connections with Greece, while also forging a cosmopolitan music scene characterized by cross-cultural creativity, gender consciousness and education and outreach. It thus demonstrates that Rebetiko is both recontextualized and transformed in London, nurtured by the city's multiculturalism. This study suggests that, by considering this scene as part of an international network, Rebetiko could be conceptualized as not only in diaspora but as a diaspora in itself, as a transnational thread that links widely dispersed and diverse musicians and enables them to create new cultural homes. This research thus contributes towards a growing literature on Rebetiko in the Greek diaspora and reflects on wider issues relating to music in contexts of migration.